The Effect of the Addition of Green Bean Puree on the Sensory Quality and Nutritional Content of Kaswi Cake - Astrid, Aisyah; Yulianti, Yeni; Riska, Nur (JUPE : Jurnal Pendidikan Mandala, 2025)
This study aimed to analyze the effect of adding mung bean puree on the sensory quality and nutritional content of kue kaswi. The research was conducted at the Pastry and Bakery Laboratory, Culinary Education Study Program, Universitas Negeri Jakarta, from August 2024 to August 2025. The experimental method was applied to kue kaswi samples with three different percentages of mung bean puree additions, namely 30%, 40%, and 50%. Based on the sensory quality analysis using the Kruskal-Wallis test, the addition of mung bean puree at 30%, 40%, and 50% did not significantly affect all evaluated sensory attributes. Statistical hypothesis testing on the proximate analysis using ANOVA showed that the addition of different percentages of mung bean puree had no significant effect on moisture content, ash content, or crude fiber content. However, it significantly affected fat content, with the best percentage being 30%, and protein content, with the best percentage being 40%. The study concluded that the optimal kue kaswi formulation with mung bean puree was the 40% formulation. Based on a sensory perspective, this formulation did not differ significantly from the control product, while from a nutritional perspective, it resulted in an increase in both fat and protein content.